Role of Quantum Correlations in Light-Matter Quantum Heat Engines - Retamal-Abarzua, J; Romero-Huenchunir, G; Alvarado-Barrios, G; Cárdenas-López, F; Albarran-Arriagada, F (American Physical Society, 2017)
We study a quantum Otto engine embedding a working substance composed of a two-level system interacting with a harmonic mode. The physical properties of the substance are described by a generalized quantum Rabi model arising in superconducting circuit realizations. We show that light-matter quantum correlation reduction during the hot bath stage and adiabatic stages act as an indicator for enhanced work extraction and efficiency, respectively. Also, we demonstrate that the anharmonic spectrum of the working substance has a direct impact on the transition from heat engine into refrigerator as the light-matter coupling is increased. These results shed light on the search for optimal conditions in the performance of quantum heat engines. © 2017 American Physical Society.